2003
DOI: 10.1200/jco.2003.10.103
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Systemic Continuous Fluorouracil and Subcutaneous Recombinant Interferon Alfa-2b for Treatment of Hepatocellular Carcinoma

Abstract: Continuous IV FU and thrice-weekly SC rIFNalpha2b are an effective treatment, especially for FLHCC, and may have a neoadjuvant role in this disease. This regimen has activity in HCC and can be tolerated even by cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
104
0
39

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(150 citation statements)
references
References 35 publications
7
104
0
39
Order By: Relevance
“…Their combination of IFN-a and 5-FU has been shown previously to be highly effective clinically (Sakon et al, 2002;Patt et al, 2003;Obi et al, 2006). This is supported by our own observation that combination therapy with IFN-a and 5-FU induced significantly more apoptosis and tumour growth inhibition than monotherapy.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Their combination of IFN-a and 5-FU has been shown previously to be highly effective clinically (Sakon et al, 2002;Patt et al, 2003;Obi et al, 2006). This is supported by our own observation that combination therapy with IFN-a and 5-FU induced significantly more apoptosis and tumour growth inhibition than monotherapy.…”
Section: Discussionsupporting
confidence: 72%
“…Recent studies have suggested that these patients may be effectively treated by combination therapy involving subcutaneous (s.c.) administration of interferon (IFN)-a and intrahepatic administration of 5-fluorouracil (5-FU) (Sakon et al, 2002;Obi et al, 2006). A Phase II trial has also revealed that continuous 5-FU infusion combined with thrice-weekly treatment with IFN-a effectively treats HCC, perhaps because the drugs together play a neoadjuvant role (Patt et al, 2003). Comprehensive genetic analyses with PCR arrays have revealed that this method may be useful for predicting whether combination chemotherapy with IFN-a and 5-FU can successfully treat HCC (Kurokawa et al, 2004).…”
mentioning
confidence: 99%
“…The effectiveness of the combination therapy of 5-FU and interferon-a on advanced HCC has been reported. 34,35 It is noted that the dose of 5-FU used in this study is 40 mg kg À1 daily for 3 days, which is much less than the amount of 5-FU used in other cases. Generally, 5-FU was given at 60-66 mg kg À1 daily in treatment of either human HCC or gastric tumors in animals.…”
Section: Discussionmentioning
confidence: 87%
“…Separate Note on FL-HCC [43][44][45][46][47][48][49][50] Because the analysis of the literature shows that NC-HCC and FL-HCC are still perceived differently on account of their different clinical presentations, courses, imaging results, and outcomes, some brief remarks about this tumor variant are made here.…”
Section: Resultsmentioning
confidence: 99%
“…48 There is some indication that adjuvant chemotherapy (a combination of 5-fluorouracil and interferon) may be useful and more applicable in these patients because they present with normal residual liver tissue. 49,50 In conclusion, at the request of the consensus conference committee, we have examined the reported results of partial liver resection and transplantation in NC-HCC patients. Although the reported experience, especially in the field of LT, is small, the (surprisingly) high tumor recurrence rate after liver resection and the few reports of successful outcomes after LT for intrahepatic recurrence after partial resection in these patients may indicate that NC-HCC is an underused indication for LT.…”
Section: Resultsmentioning
confidence: 99%